Fatores associados à participação de brasileiros em programas comunitários de atividade física: pesquisa nacional de saúde - 2019 - Alves, Marília da Silva (2024)
Introduction: The Physical Activity levels have not increased proportionally to the investments spent globally. Purpose: To identify which factors influence the participation of the population in Community Programs of Physical Activity in Brazil. Method: 20014 subjects were investigated from the National Health Survey 2019. With the outcome of participation on those Programs, the independent variables were divided into two blocks: biological (age group, gender and race/color) and sociodemographic (monthly household income, territorial area and presence of public leisure facilities close to the interviewee's residence). For data analysis, binary logistic regression was used, with a significance level of p < 0.05, through the Jamovi® software version 2.3.21. Results: In the first block, females (OR = 1.54; 95% CI: 1.40; 1.69), “elderly people” (OR = 1.10; 95% CI: 1.01; 1.21) and “non-white” people (OR = 1.51; 95% CI: 1.38; 1.66) were more likely to participate in the Community Programs than men, adults and classified as white race/color, respectively. In the second one, it was identified that those who had an income above 5 minimum wages in Brazil had reduced chances of participation by 34% (OR = 0.66; 95% CI: 0.57; 0.76) when compared to those who reported income of up to 1 minimum wage, and those who lived close to public places for leisure had a higher chances of participating in Community Programs (OR = 1.714; 95% CI: 1.52; 1.92). Conclusion: Biological and sociodemographic aspects influenced participation in Community Programs of Physical Activity, and the existence of public leisure facilities close to homes was the factor with the greatest impact evidenced in this study.